The combination of NDUFS1 with CD4+ T cell infiltration predicts favorable prognosis in kidney renal clear cell carcinoma - Wu, Dong; He, Lin; Xu, Zhe; Tian, Ruo-Fei; Fan, Xin-Yu; Fan, Jing; Ai, Jie; Bian, Hui-Jie; Qin, Wei-Jun; Qin, Jun; Li, Ling (Frontiers in Cell and Developmental Biology, 2023)
Background: Kidney renal clear cell carcinoma (KIRC) is an immunogenic tumor, and immune infiltrates are relevant to patients’ therapeutic response and prognosis. NDUFS1, the core subunit of mitochondrial complex I, has been reported to be associated with KIRC patients’ prognosis. However, the upstream regulator for NDUFS1 and their correlations with immune infiltration remain unclear. Methods: The expression of NDUFS genes in KIRC and their inﬂuences on patients’ survival were investigated by UALCAN, ENCORI, Oncomine, TIMER as well as Kaplan-Meier Plotter. miRNAs regulating NDUFS1 were predicted and analyzed by TargetScan and ENCORI. The correlations between NDUFS1 expression and immune cell infiltration or gene marker sets of immune inﬁltrates were analyzed via TIMER. The overall survival in high/low NDUFS1 or hsa-miR-320b expressed KIRC patients with or without immune infiltrates were analyzed via Kaplan-Meier Plotter. The combined NDUFS1 expression and/or CD4+ T cell infiltration on KIRC patients’ overall survival were validated by multiplexed immunofluorescence (mIF) staining in tissue microarray (TMA). Results: We found that the low expression of NDUFS1 mRNA and protein in KIRC was correlated with unfavorable patients’ survival and poor inﬁltration of CD4+ T cells. In patients with decreased CD4+ T cell infiltration whose pathological grade less than III, TMA mIF staining showed that low expression of NDUFS1 had significantly poor OS than that with high expression of NDUFS1 did. Furthermore, hsa-miR-320b, a possible negative regulator of NDUFS1, was highly expressed in KIRC. And, low NDUFS1 or high hsa-miR-320b consistently correlated to unfavorable outcomes in KIRC patients with decreased CD4+ T cell infiltration. Conclusion: Together, NDUFS1, up-regulated by decreased hsa-miR-320b expression in KIRC patients, might act as a biomarker for CD4+ T cell infiltration. And, the combination of NDUFS1 with CD4+ T cell infiltration predicts favorable prognosis in KIRC.